The mandate of the Central Bank of Nigeria - Jimoh, Lukman S.; Monetary Policy Department, Central Bank of Nigeria (Abuja, Nigeria Central Bank of Nigeria., 2012)
The understanding monetary policy series is designed to support the communication of monetary policy by the Central Bank of Nigeria (CBN). They provide a platform for explaining the basic concepts/operations required to effectively understand the monetary policy of the Bank.
Includes bibliographical references
oif 27/02/17
Ref.
Keywords: Montary policy; Banks and banking, Central; Central Bank of Nigeria; Nigeria